Competence of non-human primates to transmit Leishmania infantum to the invertebrate vector Lutzomyia longipalpis - Rodrigues de Oliveira, Ayisa (PLoS Negl Trop Dis, 2019)
Leishmaniasis is a zoonotic disease of worldwide relevance. Visceral leishmaniasis is endemic in Brazil, where it is caused by Leishmania infantum with Lutzomyia longipalpis being the most important invertebrate vector. Non-human primates are susceptible to L. infantum infection. However, little is known about the role of these species as reservoirs. The aim of this study was to evaluate the transmissibility potential of visceral leishmaniasis by non-human primates through xenodiagnosis using the phlebotomine Lu. longipalpis as well as to identify phlebotomine species prevalent in the area where the primates were kept in captivity, and assess infection by Leishmania in captured phlebotomine specimens. Fifty two non-human primates kept in captivity in an endemic area for leishmaniasis were subjected to xenodiagnosis. All primates were serologically tested for detection of anti-Leishmania antibodies. Additionally, an anti-Lu. longipalpis saliva ELISA was performed. Sand flies fed on all animals were tested by qPCR to identify and quantify L. infantum promastigotes. Eight of the 52 non-human primates were positive by xenodiagnosis, including three Pan troglodytes, three Leontopithecus rosalia, one Sapajus apella, and one Miopithecus talapoin, with estimated numbers of promastigotes ranging from 5.67 to 1,181.93 per μg of DNA. Positive animals had higher levels of IgG anti-Lu. longipalpis saliva when compared to negative animals, prior to xenodiagnosis. Captive non-human primates are capable of infecting Lu. longipalpis with L. infantum. Our findings also demonstrate the relevance of non-human primates as sentinels to zoonotic diseases. Several phlebotomine species, including Lu. longipalpis, have been identified in the area where the primates were maintained, but only one pool of Lutzomyia lenti was infected with L. infantum. This study has implications for public health strategies and conservation medicine.